Evaluation of early changes induced by diuron in the rat urinary bladder using different processing methods for scanning electron microscopy - Fava, Rafaela Marono [UNESP]; Ferragut Cardoso, Ana Paula [UNESP]; Rocha, Mitscheli Sanches da; Nascimento e Pontes, Merielen Garcia [UNESP]; Viana de Camargo, Joao Lauro [UNESP]; Cotrim Sartor de Oliveira, Maria Luiza [UNESP] (Elsevier B.V., 2015)
Diuron [3-(3,4-dichlorophenyl)-1,1-dimethylurea] is a substituted urea herbicide carcinogenic to the rat urinary bladder at high dietary levels. The suggested non-genotoxic mode of action (MOA) of diuron encompasses cytotoxicity and necrosis followed by regenerative hyperplasia. Prenecrotic swollen cells as observed under scanning electron microscopy (SEM) have been reported as early morphological alterations, putatively related to diuron cytotoxicity. However, these changes were not observed in a previous SEM study conducted in this laboratory. This study evaluated whether these early alterations are actually due to diuron cytotoxicity or artifacts related to different processing methods used for SEM analysis. Male Wistar rats were fed ad libitum with basal diet, 7.1% sodium saccharin (NaS) or 2.500 ppm diuron for seven days or 15 weeks. The urinary bladders were processed for histological and labeling indices examinations and for SEM using two different processing methods. The incidence of simple hyperplasia after 15 weeks of exposure to diuron or to NaS was significantly increased. By SEM, the incidences and severity of lesions were significantly increased in the diuron group independently of exposure time. The different SEM processing methods used allowed for visualization of swollen superficial cells after seven days of diuron exposure. Probably the absence these cells in a previous study was due to the use very few animals. Our results support the hypothesis that the swollen cell is an early key event due to diuron-induced cytotoxicity and is the result of a degenerative process involved in the non-genotoxic carcinogenic mode of action of high doses of diuron.
Keywords: Diuron[3-(3,4-dichlorophenyl)-1,1-dimethylurea]; Carcinogenesis; Early change; Rat urinary bladder; Scanning electron microscopy; Swollen cells